Anemia in Patients with Axial Spondyloarthritis is Not Associated with an Increase of Arterial Stiffness and Intima-Media Thickness (Results of a Single-Center Cross-Sectional Study) - K. N. Safarova; V. I. Makhina; K. D. Dorogoykina; A. P. Rebrov (Архивъ внутренней медицины, 2021)
Aim: to study parameters of arterial stiffness and subclinical atherosclerosis in patients with axial spondyloarthritis (axSpA) without clinically manifest cardiovascular pathology depending on the presence of anemia.Material and methods. 102 patients with axSpA (mean age – 37.7±9.8 years, axSpA duration – 13.5±8.7 years, 66 (64.7%) men) were included. The BASDAI index and C-reactive protein (CRP)-based ASDAS score were measured, the hemogram, the erythrocyte sedimentation rate (ESR), and the level of CRP were studied. Parameters of arterial stiffness were studied by oscillography and photoplethysmography, intima-media thickness (IMT) was evaluated by B-mode ultrasound according to standard protocols.Results. During analysis of pulse wave properties, no statistically significant differences in parameters of vascular wall stiffness were found in axSpA patients with and without anemia. Aortic pulse wave velocity (PWVao) in patients with anemia was 7.4±1.5 m/sec, aortic augmentation index (Aix-ao) was 19.1±13.7%, stiffness index (SI) was 8.2±1.7 m/sec; in patients without anemia – 7.4±1.4 m/sec, 17.3±10.6% and 8.8±2.0 m/sec, respectively (p >0.05 for all). IMT in patients with anemia was 0.70±0.13 cm, in patients without anemia – 0.73±0.16 cm (p >0.05). Correlation analysis was performed and significant correlations were noted between Aix-ao, PWVao, SI, IMT and age (r=0.488, r=0.516, r=0.289, r=0.461, respectively, p <0.05); Aix-ao, PWVao and the BASDAI index (r=0.243, r=0.253, respectively, p <0.05). Significant correlations between PWVao and Aix-ao (r=0.442, p <0.001), SI (r=0.273, p=0.011) and IMT (r=0.236, p=0.034) were found.Conclusion. The present study did not confirm the negative effect of anemia on vascular wall stiffness parameters and IMT in patients with axSpA. We consider that potential protective effect of anemia, due to well-known pathophysiological patterns — a decrease in blood viscosity and the induction of nitric oxide synthesis, plays an important role. Further studies are required to assess relationship between hemoglobin levels and markers of endothelial dysfunction in patients with axSpA.